Jalan Terjal Transisi Demokarsi Relasi Negara-Masyarakat Menuju Konsolidasi Demokrasi - Zamroni, M. Imam (Unisia, 2016)
The Achievement of demorcacy in Indonesia, which is considered as e collective-goal and able to cintribute ini changing Indonesia to the better situation, is struggling and facih socio-political constraints. Collustion-Corruption-Nepotism (KKN), money politicys and conflicts are even performed by elite-politician and elite-government. There for, the idea to frame a good government is merely a polemics at the elite level, yet it is on the contrary when it comes to the practice. Several politcies are mare only for the beneficial of the elite and ignoring the grass-root society, particularly in local govemment. This article analyeses the relation between the nation and the society in creating democratic climate and petitioning the society as dialectics of control through non-govemment organisation (LSM) playing the role as structure mediacy in order to avoid "elites poewer arrogance" which in turn results in non-elite policies. Hence, the society as dialectics of control acts as a balancing-powerresulting in ’a down to earth policies’ and the social control for the elite.